Bootstrapping the Shrinkage Least Absolute Deviations Estimator (European Journal of Pure and Applied Mathematics, 2010)
Kim and White (2001) studied a James-Stein type estimator that shrinks towards a data-dependent point rather than a fixed point. This was subsequently extended and applied to combining the OLS and 2SLS estimators by Judge and Mittelhammer (2004) and Mittelhammer and Judge (2005). This approach can be used to combine any two estimators in an optimal way. While the risk dominance properties of the new shrinkage estimator have been well established, a clear prescription for how to conduct inference and hypothesis testing has been missing. In this paper, we close this gap using a bootstrap approach.